Excellent Outcomes After First-Line Ablation in Post-MI Patients With Tolerated VT and LVEF >35 - Rademaker, Robert; de Riva, Marta; Piers, Sebastiaan R D; Wijnmaalen, Adrianus P; Zeppenfeld, Katja (JACC. Clinical electrophysiology, 2024)
Post-myocardial infarction (MI) patients with ventricular tachycardia (VT) are considered at risk for VT recurrence and sudden cardiac death (SCD). Recent guidelines indicate that in selected patients catheter ablation should be considered instead of an implantable cardioverter-defibrillator (ICD). This study aimed to analyze outcomes of patients referred for VT ablation according to left ventricular ejection fraction (LVEF), tolerance of VT, and acute ablation outcome. Post-MI patients without prior ICD undergoing VT ablation at a single center between 2009 and 2022 were included. Patients who presented with tolerated VT and who had an LVEF >35% were offered catheter ablation as first-line therapy. ICD implantation was offered to all patients but was subject to shared decision according to clinical presentation, LVEF, and ablation outcome. Eighty-six patients (mean age 69 ± 9 years, 84% male, mean LVEF 41 ± 9%) underwent VT ablation. In 66 patients, LVEF was >35%, of whom 51 had tolerated VT. Of these 51 patients, 37 (73%) were rendered noninducible. In 5 of 37 noninducible and in 11 of 14 inducible patients, an ICD was implanted. During a median follow-up of 40 months (Q1-Q3: 24-70 months), 10 of 86 patients had VT recurrence. The overall mortality was 27%, and 1 patient with ICD died suddenly. Among the 37 patients (none on antiarrhythmic drugs) with LVEF >35%, tolerated VT, and noninducibility, no SCD or VT recurrence occurred. Among the 14 patients with LVEF >35%, tolerated VT, and inducibility after ablation, no SCD occurred, but VT recurred in 29%. Post-MI patients with LVEF >35%, tolerated VT, and noninducibility after ablation have an excellent prognosis. Deferring ICD implantation seems to be safe in these patients.